The Effect of Using the Time Token Learning Model to Increase Students' Speaking Courage in Grade IV - Setiawan, Haris (CV Berkah Syahdin Trust, 2025)
This research was motivated by the low level of students' speaking courage during learning. The aim of this research is to see the effect of the Time Token Learning Method to increase the speaking courage of Class IV students at SDN 24 Lima Kaum. This type of research is quasi experimental design research, one-group pretest-posttest type. The population in this study was 18 class IV students at SD Negeri 24 Lima Kaum. This research uses a Liker scale instrument, the data analysis techniques used by the examiners are the t-test and n-gain test.The results of the research show that there is a significant influence of the time token learning method on students' speaking courage. The results of the t-test calculation show that to (6, 54) > tt (2,11) at an alpha value of 0.05, thus Ho is rejected. The percentage increase based on the n-gain calculation increasingly shows that the post-test results increased by 39% compared to the pre-test.